2017
DOI: 10.1093/jcbiol/rux030
|View full text |Cite
|
Sign up to set email alerts
|

Range extension of a euryhaline crab, Varuna litterata (Fabricius, 1798) (Brachyura: Varunidae), in a climate change hot-spot

Abstract: We present the first recorded range extension of a euryhaline invertebrate in the climate change hot-spot along Australia's southeastern coast. The river swimming Crab, Varuna litterata (Fabricius, 1798) (Varunidae) was found in the Coffs Harbour-Bellinger and Nambucca river basins of New South Wales, Australia in 2013, 2014 and 2016. The crabs were found during winter in shallow freshwater habitats, and may be using these habitats to avoid predators or minimise exposure to colder temperatures in deeper water.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Lapolo et al (2018) only were found in mangrove area at Tanjung Panjang Nature Reserve in Gorontalo. According to Lapolo et al (2018), V. yui is mostly found in pond areas, while V. litterata is found in freshwaters and the sea during reproduction (Mos et al 2017;Lapolo et al 2018;Susilo et al 2020). Furthermore, Carpenter and Niem (1998) stated that V. yui is a rare crab where adults are usually found in the open sea while juveniles are found in sluice gates or water embankments in mangrove areas close to land.…”
Section: Discussionmentioning
confidence: 99%
“…Lapolo et al (2018) only were found in mangrove area at Tanjung Panjang Nature Reserve in Gorontalo. According to Lapolo et al (2018), V. yui is mostly found in pond areas, while V. litterata is found in freshwaters and the sea during reproduction (Mos et al 2017;Lapolo et al 2018;Susilo et al 2020). Furthermore, Carpenter and Niem (1998) stated that V. yui is a rare crab where adults are usually found in the open sea while juveniles are found in sluice gates or water embankments in mangrove areas close to land.…”
Section: Discussionmentioning
confidence: 99%
“…This study adds to a growing list of species recorded moving south in this region ( e.g . Mos et al , 2017; Robinson et al , 2015). It is possible that warm, shallow habitats within the estuary have helped P. kaakan to overwinter in the Nambucca River at the southernmost extent of its newly expanded range, similar to the way in which the river swimming crab, Varuna litterata (Fabricius, 1798) is thought to survive in the same estuary (Mos et al , 2017).…”
Section: Figurementioning
confidence: 99%
“…Mos et al , 2017; Robinson et al , 2015). It is possible that warm, shallow habitats within the estuary have helped P. kaakan to overwinter in the Nambucca River at the southernmost extent of its newly expanded range, similar to the way in which the river swimming crab, Varuna litterata (Fabricius, 1798) is thought to survive in the same estuary (Mos et al , 2017). Estuaries in Australia's south‐east are warming at twice the rate of the ocean or atmosphere (Scanes et al , 2020), which highlights the potential for these waterways to play an important role in facilitating the poleward movement of tropical species in the region.…”
Section: Figurementioning
confidence: 99%